Pengaruh Religiositas, Keluarga, dan Digital Payment terhadap Minat dan Keputusan Berzakat di LazisMu - Budi Barata Kusuma Utami; Nurul Khaira; Fildzah Malahati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study examines the influence of religiosity, family support, and digital payment on zakat intention and decision among Muzakki of LazisMu. Using the Theory of Planned Behavior as the conceptual framework, this research positions intention as a mediating variable that explains the transition from psychological and situational factors to actual zakat-paying behavior. A quantitative approach with a survey method was employed, involving 356 respondents who had previously paid zakat through LazisMu and were familiar with digital payment systems. Data were collected using a structured questionnaire with a five-point Likert scale and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that religiosity, family, and digital payment have a significant positive effect on zakat intention. Furthermore, digital payment and zakat intention significantly influence zakat decision. The mediation analysis confirms that zakat intention significantly mediates the relationship between digital payment and zakat decision. These findings suggest that technological convenience not only directly encourages zakat payment decisions but also indirectly strengthens them by increasing individual intention. This study contributes theoretically by reinforcing the role of intention in zakat behavior and practically by providing insights for zakat institutions, particularly LazisMu, to optimize zakat collection strategies through strengthening religiosity values, family-based socialization, and digital payment innovation.